(untitled) (REVISTA SAYWA, 2024)
Stevia is a plant from South America that is cultivated in various regions. It contains a sweet component called steviol glycosides that make it a low-calorie sweetener. The use of Stevia has increased, but there is still uncertainty about its long-term effects on human health. The WHO (2022) recommends caution with non-caloric sweeteners, because they could increase the risk of cardiovascular disease and diabetes.